Guinea : Fourth Review Under the Three-Year Arrangement Under the Extended Credit Facility, and Financing Assurances Review. (IMF Staff Country Reports; Country Report ;, 2014)
EXECUTIVE SUMMARY Economic activity remained weak in early 2014. Activity was impacted by an outbreak of the Ebola virus since late 2013, but lagging structural reforms, energy shortages, and political uncertainty may also be at play. Economic growth is estimated to have been 2.3 percent in 2013, and is projected at 3.5 percent in 2014, supported by higher public investment and assuming a gradual start-up of new mining sector investment. Inflation fell to below 10 percent year-on-year in May 2014, international reserves covered 3.6 months of imports by end-2013, and the exchange rate has remained stable. Performance under the ECF-supported program remains broadly satisfactory, although progress with structural reform has been slow. All performance criteria for end-2013 were met as were all but one (the floor on priority sector spending) of the program's indicative targets for March 2014. However, the structural benchmarks for the second half of 2013 and early-2014 could not be completed as planned. The policy discussions focused on (i) the growth outlook for 2014; (ii) a supplementary budget for 2014 in light of a shortfall in revenues and new spending needs; (iii) progress in implementing structural reforms; and (iv) debt management. Risks to the program largely stem from domestic factors. New cases of Ebola have surged and spread more widely in recent months, which could affect growth in the second half of the year. The recent approval of the investment framework for the large Simandou iron ore project augurs well for a gradual pick-up in mining activity. However, renewed political tensions and uncertainty in the run-up to presidential elections, due in the second half of 2015, could risk delaying new investment. Staff supports completing the fourth review under the ECF arrangement and the financing assurances review. Completion of the review will result in a disbursement of an amount equivalent to SDR 18.36 million under the ECF arrangement.